1990
DOI: 10.1111/j.1600-0749.1990.tb00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemotherapy for B16 Melanoma: Combination Therapy of Hyperthermia, Melphalan, and CCNU in Mice

Abstract: We studied, by means of quantitative histopathological methods, the changes that took place in B16 melanoma implanted into C57BL/6J mice after combination treatment of hyperthermia, melphalan, and 1-(2-chloroethyl)-3-cyclohexyl-1-nitrosourea (CCNU). The studies were made on animals sacrificed on days 11, 18, and 25 after implantation. Tumors in treated animals showed a progressive delay in growth, a noticeably reduced number of metastases, and diminution of proliferative capacity. However, this treatment did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, prolongation of survival time was not mentioned. Vicente et al [20] conducted experiments using whole body hyperthermia on C57 BL mice and B16 melanoma and concluded that thermochemotherapy was effective in delaying tumor growth or reducing the number of metastases, but prolongation of survival was not discussed.…”
Section: Discussionmentioning
confidence: 99%
“…However, prolongation of survival time was not mentioned. Vicente et al [20] conducted experiments using whole body hyperthermia on C57 BL mice and B16 melanoma and concluded that thermochemotherapy was effective in delaying tumor growth or reducing the number of metastases, but prolongation of survival was not discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Raaphorst and Azzam [35] reported the response of transformed and normal cell lines to antimelanin compounds, 2-and 4-hydroxyanisole, alone or combined with hyperthermia or radiation. Treatment of B 16F to melanoma with the combination of hyperthermia, melphalan, and CCNU resulted in progressive delay in tumor growth, reduced metastases, and diminution of proliferative capacity [36]. As antitumor drugs fail to discriminate between normal and target tissues, any approach enabling a chemotherapeutic agent to reach its target in a selective manner would represent a major advancement in cancer chemotherapy.…”
mentioning
confidence: 99%